It's not about the money! EU funds, local opportunities, and the Brexit vote - Riccardo Crescenzi; Marco Di Cataldo; Mara Giua (London School of Economics and Political Science (LSE), European Institute, 2019)
Growing Euroscepticism across the European Union (EU) leaves open questions as to what citizens expect to gain from EU Membership and what influences their dissent for the EU integration project. This paper looks at EU Structural Funds, one of the largest and most visible expenditure items in the EU budget, to test the impact of EU money on electoral support for the EU. By leveraging the Referendum on Brexit hold in the United Kingdom, a spatial RDD analysis offers causal evidence that EU money does not influence citizens' support for the EU. Conversely, the analysis shows that EU funds contribute to mitigate Euroscepticism only where they are coupled with tangible improvements in the local labour market conditions. In order to gain support from its citizens, the European Union needs to produce tangible impacts, generating opportunities at the local level where these are felt the most by voters.
Keywords: 330; Europe; EU funds; Cohesion Policy; Brexit; Euroscepticism; RDD